CELEBRATING CULTURAL DIVERSITY AT USM INTERNATIONAL DAY - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, October 2015 – The International Office Universiti Sains Malaysia (IOUSM) recently held the International Day 2015 programme with the aim of promoting and sharing the cultures of various countries with the USM community, which also saw the attendance of the Deputy ViceChancellor (Academic and International Affairs), Professor Dato’ Dr. Ahmad Shukri Mustapa Kamal.